The Influence of Proportion of Yellow Pumpkin (Cucurbita Moschata) Flour and Red Rice (Oryza Glaberrima) Flour towards Organoleptic Properties of Food Bar - Miranti, Mauren G.; Helga, J.B. (INVOTEC, 2018)
Food bar is food with a bar-like shape which contains adequate energy and nutrition. This study aims to determine the right proportion between red rice flour and yellow pumpkin flour as well as to analyze the influence of said proportion towards organoleptic properties of the food bar. The proportions between red rice flour and yellow pumpkin flour used in this study are 40% and 60%, 50% and 50%, and 60% and 40%. With those varying proportions, the food bars are organoleptically tested based on their color, smell, taste, blendability and favorite level. The study shows that the proportion of red rice flour and yellow pumpkin flour has an impact on the organoleptic properties of the food bar such as the taste, blendability, and favorite level. However, the proportion has no effect on the color and smell of the food bar. The best food bar product contains the proportion of 50% red rice flour and 50% yellow pumpkin flour. Nutrions found per 100g are 144.2 kcal energy, 26g carbohydrate, 15.38mg calcium, 4.56g fat, 2.18g protein, 34.32mg phosphor, 83.04 RE vitamin A, 0.04mg vitamin B1, 13.26mg vitamin C.